2008
DOI: 10.1515/pteridines.2008.19.1.12
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Neural Tube Defects in Sétif University Maternity Hospital, Algeria-3 Years Review (2004-2006)

Abstract: Neural tube defects (NTDs) including spina bifida, anencephaly and encephalocele are among the most common birth defects, with high associated mortality and morbidity. There are no data concerning the incidence, associated anomalies, treatment and outcome of NTDs in Algeria. The objective of this study is to analyse data on NTD cases from 2004-2006 at Sétif Hospital, a hospital with 8,000-10,000 deliveries annually. A retrospective chart review of patients with NTDs was performed, who were born at Sétif Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
0
20
1
Order By: Relevance
“…From the research conducted in Algeria for a period of three years (2004)(2005)(2006), it has been concluded that consanguinity is a factor in fetuses with NTDs in 13% of the cases (28/215 cases), which is twice less than our results [18].…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…From the research conducted in Algeria for a period of three years (2004)(2005)(2006), it has been concluded that consanguinity is a factor in fetuses with NTDs in 13% of the cases (28/215 cases), which is twice less than our results [18].…”
Section: Resultscontrasting
confidence: 63%
“…In Algeria, the established NTD rate is 0.75 per 1000 births where, in 13% of the cases, incest was found [18]. The influence of the seasons of conception for the presence of NTDs has been the subject of numerous studies with varying results [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Our research is the first in Algeria, which studied NTD patients in order to determine the association of the T allele with NTD in the region of Sétif, where NTD are highly prevalent (Houcher et al, 2008). The MTHFR C677T gene polymorphism was neutral in our population.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the MTHFR genotype of the father also contributes to the risk of NTD (Blom, 1998) The thermolabile MTHFR C677T variant is a risk factor for NTD in some but not all populations (Botto and Yang, 2000) and is associated with low folate and elevated www.intechopen.com homocysteine levels. The high prevalence of the MTHFR 677T allele (17%) (Bourouba et al, 2009), the higher risk of NTD (7.5 per 1,000 births) (Houcher et al, 2008) and lower daily folate intake (69%) of less than the reference nutrient intake for folate (Houcher et al, 2003), i.e. a combination of genetic and nutritional factors, may therefore play a role in the NTD rate in this region of Algeria, although the mechanism, by which the genotype or folate status increases the risk of NTD is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Spina bifida with myeloschisis may result from a defect that is caused by a local overgrowth of the neural plate. As a result, the caudal neuropore fails to close at the end of the fourth week [ 1 , 6 ]. Due to the tethering of the spinal cord, the incidence of hydrocephaly is expected to be very high in each case of spina bifida cystica [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%